Framework for corporate solar energy production - Bencző, László; Tóth, Tamás; Takács, Péter; Baranyai, Gergő (Studia Mundi – Economica, 2020)
The production and use of solar energy is increasingly important not only in the private or institution sector, but in the corporate sector as well. However, there are still some elements in the regulatory system that need to be optimized. In our study, we intend to highlight these elements, and to make proposals for improving the effectiveness of those processes that currently pose a challenge for the operators. In addition to an overview of the regulatory system, in the course of decision shaping, we propose the possibility of using vanadium battery as a solution for energy storage, since this technology may be suitable for use under the climate conditions of our country, bot in case of the FIT (feed-in tariff) and the RESS systems (renewable energy support scheme).